Study & Experimental Analysis of Pervious Concrete in Low Volume Roads: Investigating the Durability and Water Absorption of Pervious Concrete for Low Volume Roads (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Pervious concrete is a special high porosity concrete used for flatwork applications that allows water from precipitation and other source to pass through there by reducing the runoff from a site and recharging ground water levels. Durability and Water Absorption are important properties of Pervious Concrete. It is a special type of concrete having a high void content of about 30 due to use of special admixture silica fumes (powder form), is becoming popular nowadays due to its potential to reduce the runoff to the drainage systems which can provide a water flow rate around 0.34 cmsecond. This paper represents the experimental methodology and experimental results related to durability and water absorption. This investigation should be carried out at the end of 14 days for water absorption and 28 days for durability. Different concrete mix proportion such as 13, 14 and 15 with size of gravel such as 20 mm passing and 12 mm retained should be used to check both these properties of pervious concrete. Test results indicates that pervious concrete made by 13 concrete mix proportion has more durability and less water absorption and pervious concrete made by 15 mix proportion has more water absorption and less durability that’s why durability and water absorption are inversely proportional to each other.